Legal Study Of Criminal Acts Of Electricity Theft Reviewed Based On Law No. 30 Of 2009 Concerning Electricity - Rinaldi Kalman; Kusno Kusno; Ahmad Ansyari Siregar (International Journal of Science and Environment (IJSE), 2025)
The purpose of this study is to find out and understand the Regulations on Electricity Reviewed Based on Law No. 30 of 2009 Concerning Electricity and Criminal Liability for Perpetrators of Electricity Theft. The type of research used is normative research, with an approach method through legislation. Discussion Results: First, the Regulations on Electricity Reviewed Based on Law No. 30 of 2009 Concerning Electricity are regulated in CHAPTER I to CHAPTER XVII. The Regulations regulate: General Provisions; Principles and Objectives; Control and Business; Management Authority; Utilization of Primary Energy Sources; General Electricity Plan; Electricity Business; Land Use Permits; Selling Prices, Network Rentals, and Electricity Tariffs; Environment and Engineering; Guidance and Supervision; Investigation; Administrative Sanctions; Criminal Provisions, Transitional Provisions; Closing Provisions. Second, Criminal liability for perpetrators of electricity theft is regulated in Article 51 paragraph (3) and Article 53 of Law Number 30 of 2009 concerning Electricity. Article 51 Paragraph (3) which reads "Any person who uses electricity that is not his right unlawfully shall be punished with imprisonment of a maximum of 7 (seven) years and a maximum fine of Rp2,500,000,000.00 (two billion five hundred million rupiah). And Article 53 which states: "Any person who carries out business activities supporting electricity services without a permit as referred to in Article 25 paragraph (1) shall be punished with imprisonment of a maximum of 5 (five) years and a maximum fine of Rp2,000,000,000.00 (two billion rupiah)."